Original articleMorphological changes and selective loss of motoneurons in the lumbar part of the spinal cord in a rat model of familial amyotrophic lateral sclerosis (fALS) - Gadamski, Roman; Chrapusta, Stanisław J.; Wojda, Renata; Grieb, Paweł (Folia Neuropathologica, 2006)
Morphological alterations and the course of changes in motoneuron counts were studied by light microscopy (cresyl violet staining) in the L2/L3 region of the spinal cord of hemizygotic transgenic rats carrying the amyotrophic lateral sclerosis-associated mutant human gene for Cu,Zn superoxide dismutase (hSOD1 G93A ) and of their non-transgenic littermates. In 60-day old transgenic rats, a few ischaemic-looking α-motoneurons and occasional vacuolization and accumulation of tigroid in some of the cells were apparent. On day 93 of life more distinct cellular pathology was found in transgenic rats, including moderate gliosis, neuronophagy of α-motoneurons, and occasional neuronophagy of γ-motoneurons. In 120-day-old transgenic rats, abundant gliosis and profound neuronophagy of α-motoneurons were observed combined with occasional neuronophagy of other cells. Some loss of α-motoneurons was also apparent in 120-day-old non-transgenic littermates of the transgenic rats. No difference in α-motoneuron and γ-motoneuron counts was found between the rats on day 60 of life (early presymptomatic stage of the model disease in the transgenic rats). At 93 days of age (late presymptomatic stage), α-motoneuron count, but not γ-motoneuron count, tended to be lower (p=0.06) in the transgenic rats. On day 120 of life (symptomatic stage), α-motoneuron count in the transgenic rats was about half that in their nontransgenic littermates (p<0.001); at this time point the relative decline in α-motoneuron number in the former was 57% (day 120 versus day 60; p<0.001). A smaller decline in α-motoneuron count was also found in nontransgenic rats (day 120 vs day 60: 24%, p<0.05); this was not associated with the emergence of neurological symptoms or distinct changes in the cell morphology of the spinal cord region studied.